Intraoperative Pancreatoscopy During Robotic Pancreatoduodenectomy and Robotic Distal Pancreatectomy for Intraductal Papillary Mucinous Neoplasm with Involvement of the Main Pancreatic Duct - Zhi Ven Fong, MD, MPH; Maurice J.W. Zwart, MD; Myrte Gorris; Rogier P. Voermans; Roy L.J. van Wanrooij; Thijs Wielenga; Marco del Chiaro, MD; Urban Arnelo, MD, PhD; Freek Daams, MD; Olivier R. Busch, MD, PhD; Marc G. Besselink, MD, MSc, PhD (Annals of Surgery Open, 2023)
Background:. Intraductal papillary mucinous neoplasm (IPMN) with involvement of the main pancreatic duct usually requires surgical resection. Consensus is lacking whether to partially or completely resect the pancreatic portion with a dilated main pancreatic duct. Intraoperative pancreatoscopy may be useful to determine the extent of IPMN to tailor surgical resection and was recently studied in a large prospective international study. IPMN is increasingly utilized using a robotic approach. Studies describing the technical approach to intraoperative pancreatoscopy in robotic pancreatoduodenectomy and robotic distal pancreatectomy are lacking. Methods:. During robotic pancreatoduodenectomy, pancreatoscopy is performed once the pancreas neck is transected. The scope is advanced via a laparoscopic port into the left and right-sided pancreatic duct, guided by robotic graspers. During robotic distal pancreatectomy, pancreatoscopy is performed before complete parenchymal transection. The scope is advanced through an anterior ductotomy to examine the duct and guide the pancreatic transection line. Tips and tricks how to perform the procedure efficiently without complications are detailed. Results:. In total, 28 robot-assisted pancreatoscopies were performed during robotic pancreatoduodenectomy and robotic distal pancreatectomy. No intraoperative complications resulting from the intraoperative pancreatoscopy were noted. In the 2 described procedures, the added time required to perform the pancreatoscopy was 6 and 17 minutes, respectively. Both patients recovered without complication and were discharged on postoperative day 5 for the robotic pancreatoduodenectomy and day 6 for the robotic distal pancreatectomy. Conclusions:. Intraoperative pancreatoscopy can be safely performed during both robotic pancreatoduodenectomy and robotic distal pancreatectomy for IPMN with the involvement of the main pancreatic duct. An international prospective study has recently been completed with this technique.